WATER MANAGEMENT IN DISTRICT 011, THE WATERING MODULES OF ACÁMBARO AND SALVATIERRA, GUANAJUATO MÉXICO - Aguilar-Sánchez, Genaro; De La Cruz-Ángeles, Javier (Revista Geográfica de América Central., 2016)
Water management is essential for food production; therefore, this paper analyzes two irrigation modules -Acámbaro and Salvatierra, which belong to the irrigation district 011. The analysis shows the water use management, the different practices performed, the common problems, and the specific differences; consequently, the research was focused on key informants. The main issues faced by the irrigation modules are lack the of users’ awareness, little irrigation modernization, lack of land leveling programs, zero measurement of water given to each user, and abuse in extracting groundwater. All these problems seem to have a solution; the challenge is then to find appropriate mechanisms to implement these solutions.